On the Accuracy and Uncertainty of Coronal Mass Ejection 3D Reconstructions Depending on the Number of Viewpoints in the Heliosphere - Eleni Nikou; Jie Zhang; Suman K. Dhakal; Matthew Dupertuis (The Astrophysical Journal, 2025)
This paper presents a systematic study that focuses on how the number of viewpoints distributed in the heliosphere affects the accuracy and uncertainty of the 3D geometric coronal mass ejection (CME) measurements. An efficient nonmanual minimization-based fitting technique that is different from the manual methods widely used in the community is developed. It uses the MPFIT minimization IDL routine and searches for the optimized model point clouds that best fit the observed CME leading edges from one, two, or three viewpoints using a set of combinations of observations provided by the Solar Terrestrial Relations Observatory and Solar and Heliospheric Observatory. The technique also provides a robust calculation of uncertainties of the CME geometric parameters that is lacking in manual methods. Three well-known geometric models, the cone, graduated cylindrical shell, and spheroid shock, are used. All three models depend on geometric parameters that govern the CME propagation direction and size. Sample cases of a halo, partial halo, and limb CMEs as seen from the Earth are used in the fitting and uncertainty calculation. It is found that, after adding a second viewpoint off the Sun–Earth line, the uncertainties drop significantly, while the addition of the third viewpoint adds limited benefits. This study shows that the minimization fitting method provides a robust, fast, and straightforward way to define the CME geometric parameters along with their uncertainties for individual events, which shall provide the necessary data constraints for ensemble predictions of CME evolution. It also underlines the importance of having a permanent observatory off the Sun–Earth line for operational space weather prediction.